Pnictogen-halide semiconductors for photovoltaics - Liu, P (2025)
Indoor photovoltaic (IPV) development has garnered increasing interest in recent years because of the potential to sustainably provide energy to the billions of autonomous devices part of the Internet of Things (IoT) ecosystem. The emission spectra of indoor light sources are narrower and blue-shifted compared to the standard terrestrial outdoor AM 1.5G solar spectrum, which is the reference spectrum for standard testing of solar energy conversion systems, with a specified standard irradiance of 1000 W/m2[1]; AM stands for air mass coefficient. The intensity of indoor light sources is approximately three orders of magnitude lower than 1-sun illumination [2, 3]. Crystalline silicon photovoltaics (PVs), which dominate the outdoor PVs industry, are not suitable for indoor light harvesting because of their low bandgap and high dark currents, which limits their performance under indoor illumination. The current commercial IPV devices are hydrogen passivated amorphous silicon (a-Si:H), but have low efficiencies, typically in the range of 4.4% to 9.2%[4-8]. There is significant scope, therefore, to develop alternative classes of light absorbers that could more efficiently harvest energy from indoor lighting.